Time-resolved diffraction of shock-released SiO2 and diaplectic glass formation. Issue 1 (December 2017) - Gleason, A.; Bolme, C.; Lee, H.; Nagler, B.; Galtier, E.; Kraus, R.; Sandberg, R.; Yang, W.; Langenhorst, F.; Mao, W.
Abstract Understanding how rock-forming minerals transform under shock loading is critical for modeling collisions between planetary bodies, interpreting the significance of shock features in minerals and for using them as diagnostic indicators of impact conditions, such as shock pressure. To date, our understanding of the formation processes experienced by shocked materials is based exclusively on ex situ analyses of recovered samples. Formation mechanisms and origins of commonly observed mesoscale material features, such as diaplectic (i.e., shocked) glass, remain therefore controversial and unresolvable. Here we show in situ pump-probe X-ray diffraction measurements on fused silica crystallizing to stishovite on shock compression and then converting to an amorphous phase on shock release in only 2.4 ns from 33.6 GPa. Recovered glass fragments suggest permanent densification. These observations of real-time diaplectic glass formation attest that it is a back-transformation product of stishovite with implications for revising traditional shock metamorphism stages. Our understanding of shock metamorphism and thus the collision of planetary bodies is limited by a dependence on ex situ analyses. Here, the authors perform in situ analysis on shocked-produced densified glass and show that estimates of impactor size based on traditional techniques are likely inflated.